Peran Media Sosial Bagi Penguatan Bisnis UMKM di Kota Serang Banten - Bambang Arianto; Herry Sofyan (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2022)
This study aims to elaborate on the role of social media for strengthening the business model of Micro, Small and Medium Enterprises (MSMEs) in Serang City, Banten Province. The era of the digital economy has made the role of social media increasingly influencing all civic activities. This makes a high dependence on social media for various civic business activities. Social media is then used as the main means of digital marketing as well as product and service branding. Social media is also used as a means of business communication with the aim of strengthening relations between business people and customers and consumers. This study uses explanatory qualitative methods and observations of MSME activists in Serang City, Banten Province. This research states that social media with all its benefits has contributed to strengthening digital marketing models, business promotion, new knowledge, business communication and branding strategies for MSMEs. However, knowledge of social media governance is needed so that it can become the main alternative in strengthening business for MSMEs in Serang City, Banten Province.